2012
DOI: 10.1038/onc.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 controls angiogenesis through regulation of ERK phosphorylation

Abstract: BAG3 is a co-chaperone of the heat shock protein (Hsp) 70, is expressed in many cell types upon cell stress, however, its expression is constitutive in many tumours. We and others have previously shown that in neoplastic cells BAG3 exerts an antiapoptotic function thus favoring tumour progression. As a consequence we have proposed BAG3 as a target of antineoplastic therapies. Here we identify a novel role for BAG3 in regulation of neo-angiogenesis and show that its downregulation results in reduced angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
5
39
1
1
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Moreover, BAG3 regulated angiogenesis of HCC cells through ERK phosphorylation, in accordance with previous studies. 12 Earlier work showed that autophagy-related genes could downregulate angiogenesis; 18,19 however, in our study, knockdown of BAG3 could downregulate the autophagy process. According to these data, a possible molecular In conclusion, we demonstrated that BAG3 knockdown is associated with the invasiveness of HCC cells, potentially by inhibiting EMT and angiogenesis.…”
Section: Bag3 Function In Human Hepatocellular Carcinomacontrasting
confidence: 45%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Moreover, BAG3 regulated angiogenesis of HCC cells through ERK phosphorylation, in accordance with previous studies. 12 Earlier work showed that autophagy-related genes could downregulate angiogenesis; 18,19 however, in our study, knockdown of BAG3 could downregulate the autophagy process. According to these data, a possible molecular In conclusion, we demonstrated that BAG3 knockdown is associated with the invasiveness of HCC cells, potentially by inhibiting EMT and angiogenesis.…”
Section: Bag3 Function In Human Hepatocellular Carcinomacontrasting
confidence: 45%
“…This finding is in accordance with previous studies in glioblastoma and thyroid carcinoma. 10,34 A potential mechanism is that BAG3 knockdown may decrease the tumor neovascularization that supplies the tumor cells with nutrients, 12 thereby inhibiting the tumorigenicity and metastasis of HCC cell lines in vivo. In the current study, we measured CD34 and VEGF expression in vivo.…”
Section: Bag3 Function In Human Hepatocellular Carcinomamentioning
confidence: 99%
“…ERK1/2 binds to MVP, suggesting that vaults may serve as signaling scaffolds for ERK1/2 or in the transport of phospho-ERK1/2 to the nucleus (40). Bag3 has being shown to stabilize the interaction of ERK1/2 with Dual-specificity Phosphatase 1 in HUVECs and in this case, its removal resulted in G1 block not apoptosis implying its role is cell dependent (41). Our results suggest that MVP and Bag3 promote resistance to apoptosis in senescent cells by promoting or sustaining activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a broader role for BAG3. For example, BAG3 regulates epithelial-mesenchymal transition and angiogenesis through ERK phosphorylation [57, 107]; induces epithelial-mesenchymal transition through activation of the transcription factor ZEB1 [108]; and modulates the activity of the transcription factors FoxM1 and Hif1α, the translation regulator HuR and the cell cycle regulators p21 and survivin [109]. BAG3 also downregulates the microRNA-29b which leads to upregulation of the anti-apoptosis protein Mcl-l leading to resistance to anticancer drugs [110].…”
Section: Autophagy and Apoptosismentioning
confidence: 99%